Respon Pertumbuhan Ayam Kampung Super yang Mengkonsumsi Pakan Komplit Mengandung Tepung Daun Kelor - Osias Ndun; Catootjie Lusje Nalle; Cytske Sabuna (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
The trial had the objective to examine the safe level of Moringa meal used for 10 weeks old super kampong chickens. The super kampong chickens in the trial were distributed into 20 experimental pens (8 chickens/replication). The study was conducted under completely randomized design with four treatments and five replications. The treatments were as follows: P0 (control), P1 (5% MLM), P2 (7.5% MLM), and P3 (10% MLM). The statistical analysis revealed that the treatment considerably influenced the diet intake (DI), body weight gain (BWG), as well as feed per gain (FPG). The use of Moringa powder produced better bird’s performance than those allotted in basal diets. In conclusion, 1) the safe inclusion level of Moringa powder in a balance nutrient diet was up to 10% 2) the addition of Moringa increased the palatability of the diets, leading to the improvement of DI, BWG and FPG.